2000
DOI: 10.1159/000053254
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Serum Level of Leptin and Life-Style Habits in Japanese Men

Abstract: Aims/Methods: To investigate whether smoking affects the serum level of leptin, 708 male workers aged 25–65 years old were cross-sectionally surveyed. Results: Multiple regression analysis indicated that among the various parameters examined, the level of leptin was positively associated with the body mass index and the levels of insulin, total cholesterol and uric acid, and was inversely associated with physical activity and the level of creatinine. The partial correlation coefficient of leptin was highest ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 51 publications
1
13
0
2
Order By: Relevance
“…Finally, although body fat mass is the most important variable that controls circulating leptin and adiponectin, there is great heterogeneity in the concentrations of these adipokines at any given level of body fat, and differences between populations may contribute to the discrepant results from different populations. In support of this, the relationship between leptin and smoking has been found to be different in different populations [1,15,16,26] .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Finally, although body fat mass is the most important variable that controls circulating leptin and adiponectin, there is great heterogeneity in the concentrations of these adipokines at any given level of body fat, and differences between populations may contribute to the discrepant results from different populations. In support of this, the relationship between leptin and smoking has been found to be different in different populations [1,15,16,26] .…”
Section: Discussionmentioning
confidence: 90%
“…However, despite its association with weight reduction and known association between smoking cessation and weight gain, studies on the association between smoking and adipokines have often yielded conflicting results. For example, with regard to leptin, the main adipokine regulating body weight, studies have often shown contradictory results with some studies showing a decrease [1,[12][13][14]] , no effect [15,16] or even an increase [17] . We had shown in a previous study that smoking sheesha and cigarettes have adverse metabolic effects [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Mild to moderate leukocytosis is common among SCA patients and this has been attributed to re-distribution of leukocytes from marginal pool to a systemic pool of granulocytes, while moderate lymphocytosis and monocytosis have been implicated as markers of inflammation in SCA patients [1,2,4,47,48]. A study by Wilson et al [50] revealed a positive correlation between leptin level and WBC count, while Togo et al [51] showed that leptin associates negatively with haemoglobin. In this study, we did not find significant correlation between leptin and these haemotological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…BMI, subcutaneous thickness, and other indicators of body fat, together with gender, clearly illustrate the differences in leptin levels (7, 8). The factors such as physical activity that reduce adipose tissue also diminish levels of leptin (9, 10, 11, 12). However, despite its association with weight reduction, tobacco consumption has shown contradictory results (9, 13, 14, 15, 16, 17).…”
Section: Introductionmentioning
confidence: 99%
“…The factors such as physical activity that reduce adipose tissue also diminish levels of leptin (9, 10, 11, 12). However, despite its association with weight reduction, tobacco consumption has shown contradictory results (9, 13, 14, 15, 16, 17). Factors such as hypertension that are associated with an increase in adipose tissue are associated with increases in the serum levels of leptin (18).…”
Section: Introductionmentioning
confidence: 99%